Field notes contributed by Chris Edwards, summer 2000 - Edwards, Chriset al (2000)
Summer report of birds found in eastern Iowa contributed by Chris Edwards. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2000. Epson - sheet feed